Perceived Organizational Support Mediates The Effect of Job Insecurity on Organizational Citizenship Behavior at Adiwana Unagi Suites - Ni Putu Vera Andriyanti; IB Raka Suardana (International Journal of Social Science and Business, 2023)
Facing the Covid-19 pandemic, the tourism sector, especially in the hospitality sector, must make several adjustments in order to survive, one of which is reducing the number of employees. This condition causes the remaining employees to do extra work so that the company can run. This study aims to determine the role of perceived organizational support in mediating the effect of job insecurity on organizational citizenship behavior. This research was conducted at Adiwana Unagi Suites. The population in this study were 63 employees. The method of determining the sample uses the census method so that the entire population becomes the sample. Data analysis used is SEM-PLS and Sobel test. The results of this study indicate that job insecurity has a negative and significant effect on organizational citizenship behavior. Job insecurity has a negative and significant effect on perceived organizational support. Perceived organizational support has a positive and significant effect on organizational citizenship behavior. Perceived organizational support is able to mediate negatively the effect of job insecurity on organizational citizenship behavior.